Fumarate reduction and product formation by the Reiter strain of Treponema phagedenis. - George, H A (American Society for Microbiology (ASM), 1982)
The catabolic pathways for butyrate, acetate, succinate, and ethanol formation by the Reiter strain of Treponema phagedenis were investigated. Enzyme activities were demonstrated for glucose catabolism to pyruvate by the Embden-Meyerhof-Parnas pathway. Butyrate formation from acetyl-coenzyme A (acetyl-CoA) does not generate ATP by substrate level phosphorylation and involves NAD+-dependent 3-hydroxybutyryl-CoA dehydrogenase and NAD(P)+-independent butyryl-CoA dehydrogenase activities. Butyrate is formed from butyryl-CoA in a CoA transphorase reaction. Phosphate acetyltransferase and acetate kinase activities convert acetyl-CoA to acetate. An NADP+-dependent alcohol dehydrogenase participates in ethanol formation; however, the manner in which acetyl-CoA is reduced to acetaldehyde is unclear. A membrane-associated fumarate reductase was found which utilized reduced ferredoxin or flavin nucleotides as physiological electron donors. Additional electron carriers may also be involved in electron transfer for fumarate reduction. Strains of Treponema denticola, T. vincentii, and T. minutum utilized fumarate without succinate formation, whereas strains of T. phagedenis and T. refringens formed succinate from exogenously supplied fumarate.